MODIFIED BENTONITE AS FUNCTIONAL MATERIAL FOR SEPARATION OF CHROMIUM SPECIES BY FIA-AAS TECHNIQUE - AMINAH (NIM: 30512020), SITTI
Chromium (Cr) is one of the heavy metals which element and its compounds are widely used in electroplating, leather tanning, paint and wood preservation industries. Cr is one of the trace elements which is essential and toxic to living things depending on their chemical form. Cr(VI) has a higher toxicity than Cr(III). The presence of Cr species in particular environments is generally at very low concentrations, thus required highly sensitive analysis method or pre-concentration and separation methods prior to analytical instrumentation measurement. The different levels of toxicity of the chromium species, the limitations of the simultaneous analysis method for Cr species, complicated analysis process and complex matrixes which become one of the reasons for developing an analytical methods of Cr species. The method developed is expected to have a good analytical performance, with simple equipment, inexpensive and environmentally friendly. Various strategies are carried out in the effort to find and develop the method of Cr speciation, such as the utilization of functional materials as adsorbents in the FIA system through the modification of natural or by synthetic materials. Bentonite is one of potentials IndonesiaÃ‚Â’s natural materials which contains high montmorillonite, layered structure, porous, good mechanical and chemical stability, large surface area and high cation exchange capability. This material has not been optimally utilized thus encouraging the utilization efforts of bentonite such as adsorbent material. However, the bentonite active site is not uniform and the ability to adsorb anions is very low. Thus, modification is required to be able to retain Cr(III) and Cr(VI) simultaneously. The development of functional materials begins with modifying bentonite using three types of cationic surfactants that have different carbon chain length i.e., tetra-methyl ammonium bromide (TMAB), decyltrimethylammonium bromide (DTAB) and cetyltrimethylammonium bromide (CTAB) and chitosan as a modifier. The success of the modification process is shown by the difference in the results of material characterization before and after modified using various methods such as: spectrophotometry Infrared (FTIR), X-ray diffraction (XRD), scanning electron microscope (SEM), fluorometric X-rays (XRF), Zeta potential and thermogravimetric analysis (TGA). Evaluation of the adsorbent performance for Cr species retention was studied by batch and dynamic (column) method through optimization of several parameters, while the determination of chromium species concentration in water was conducted using atomic absorption spectrophotometric (AAS) method. The modification process can increase the retention capacity of bentonite toward Cr species and is influenced by the type and amount of modifier used. The use of CTAB and chitosan modifiers simultaneously demonstrated a synergistic effect. So that the modified CTAB-chitosan bentonite functional material (Bt-MCCs) was used as the selected adsorbent material and optimized adsorption parameter subsequently used in the development of FIA techniques with AAS as an element selective detector. The amount of Cr(III) and Cr(VI) adsorbed on Bt-MCCs is strongly influenced by pH and Cr species. From the results obtained, it was found that the optimum pH for Cr(III) adsorption occurred at pH-5 and Cr(VI) at pH 3. Bt-MCCs could be used for selective separation of Cr species and also at the same time allowed to adsorb Cr species of aqueous solution simultaneously. Selective separation of Cr species may be performed if the solution is conditioned at pH 2 where Cr(VI) will be retained much larger than Cr(III). For the simultaneous adsorption of Cr(III) and Cr(VI) can be done at pH 5 conditions where these two species will be adsorbed up to 98%. The retention capacity of the batch method toward Cr species was greater than the dynamic method (16.98/3.13 mg/g for Cr(III) and (15.38/2.25 mg/g) for Cr(VI)). The adsorption isotherm model followed the Langmuir and Freundlich models. Based on the (n) values obtained on the Freundlich isotherm and the (RL) values obtained from the Langmuir isotherms indicate that the Cr species adsorption process tends to be favored, while the adsorption kinetics follows the pseudo-second order models. Development of FIA-AAS technique in this study is generally aims to develop and evaluate the use of functional materials modified bentonite as adsorbents in FIA-AAS techniques for separation, pre-concentration and trace analysis of Chromium species. A value of absorbance detector signal further processed by using PowerChrom(R) and Origin 8.5 software to produce fiagram form of plot between the signal heights versus time. The separation, pre-concentration and trace analysis of the Cr species in the water sample have been successfully performed using a mini-column of Bt-MCCs in the FIA system which is integrated directly (online) with AAS at optimum measurement conditions. Carrier pH-5, flow rate 2mL/ minute, 0.2 g mas of adsorbent and column length 5 cm with eluent ammonia 0.5M and 2M nitrate acid respectively 0.5 mL and sample volume of 1 mL were used to obtain measurement results with good analytical performance. Analytical performance of the develop method is described as repeatability linearity, detection limit and accuracy of Cr(III) analysis were 1.78%; 0.9975 in the concentration range 50-500 μg/L and 2.76 μg/L; 98.84% respectively, whereas for Cr(VI) were 0.60; R2 0.9926 in the concentration range 50-500 μg/L and 2.42 μg/1; 100.73% respectively. Flow Injection Analysis performance including enrichment factor, concentration efficiency and consumptive index were 10 times; 12 h-1 and 12 mL, respectively. The analysis results of Cr species concentration in river water samples of Cidurian, West Java, Indonesia is 38.67 Ã‚Âµg/L for Cr(III) and 27.33 Ã‚Âµg/L for Cr(VI), with the percent recovery of 98.84% for Cr(III), and 100.73% for Cr(VI). The results show that matrix effects do not have a significant influence on the analysis of Cr species, so it can be concluded that the Bt-MCCs functional materials developed can be used for separation, pre-concentration and trace analysis of Cr(III) and Cr(VI) in river water samples. Separation technique that is able to perform pre-concentration and can simplify the sample matrix like the one developed in this study can be used as an alternative in speciation analysis Cr. The main advantage of this technique is that the equipment is simpler so that it can be implemented in most laboratories in Indonesia, the analysis time is relatively short, easy to automate, the sample volume is small and easy to combine with various detection techniques, and the cost of analysis is cheaper.